Menggagaskan Bugis dan Keislaman menurut Christian Pelras - Patan, Kosmas Ambo (Perspektif, 2007)
Bugis Society has a very long tradition of international trade. Because of this reason, the society has long contact with international community. Apart from trading, there were also efforts to spread certain religions. Although for centuries many Christian missionaries passed by the place, the Moslem missionaries seem to be more successful in coverting the locals. Since then, Islam becomes the main religion of the local communities and plays a major role to shape the modern Bugis society. This is the background of the research done by Christian Pelras, a French anthropologist. Based on the research done by Pelras, the author tries to picture how Islam golo has influenced the local communities, change their attitude and way of life. Six First of all, it changes the social system, the concept of belongings, religious system, law and social life. Although the "Shari'ah" (Islamic Law) is regarded as the major law, it is discovered that syncretism is still existed and plays significant roles in the life of ordinary people. The author highlihgts the fact that this situation could lead to a conflict with those who try to keep the orthodoxy of Islam teaching. The author insists that the finding fact could serve as a good lesson for Indonesian national community to maintain the plurality, as the people in Bugis have lived for centuries.